A 5° × 5° deep H i survey of the M81 group − II. H i distribution and kinematics of IC 2574 and HIJASS J1021+68. Issue 2 (12th February 2020) - Sorgho, A; Chemin, L; Kam, Z S; Foster, T; Carignan, C
ABSTRACT: We analyse the eastern region of a 5° × 5° deep H i survey of the M81 group containing the dwarf galaxy IC 2574 and the H i complex HIJASS J1021+68, located between the dwarf and the M81 system. The data show that IC 2574 has an extended H i envelope that connects to HIJASS J1021+68 in the form of a collection of small clouds, but no evident connection has been found between IC 2574 and the central members of the M81 group. We argue, based on the morphology of the clouds forming HIJASS J1021+68 and its velocity distribution, that the complex is not a dark galaxy as previously suggested, but is instead a complex of clouds either stripped from, or falling on to the primordial H i envelope of IC 2574. We also use the deep H i observations to map the extended H i envelope around IC 2574 and, using a 3D tilted-ring model, we derive the rotation curve of the galaxy to a larger extent than has been done before. Combining the obtained rotation curve to higher resolution curves from the literature, we constrain the galaxy's dark matter halo parameters.